If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5c + 15 = 25 Reorder the terms: 15 + 5c = 25 Solving 15 + 5c = 25 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 5c = 25 + -15 Combine like terms: 15 + -15 = 0 0 + 5c = 25 + -15 5c = 25 + -15 Combine like terms: 25 + -15 = 10 5c = 10 Divide each side by '5'. c = 2 Simplifying c = 2
| y=4x-17-2y | | 5x-10+12x-14=180 | | 4y+2=3y-6 | | 99-7x=29x+19 | | 13-9x=81-37x | | 13-9x=81-36x | | t*-8=-3*8 | | -g*6=-14 | | A^2b^2-b^2=0 | | y*10=-2*5 | | -18-4x=14-8x | | -19-6x=9-10 | | x*5=-4 | | 82-6x=10x+18 | | 29=6y-25 | | 6+7e-4=4e+8 | | 10(w+5)=5(w-2) | | 12-10x=57-45x | | 5x+6=-46-8x | | 5(t+11)-5=35 | | 10r^2-19r-15= | | 14-8x=113-29x | | 172-4x=32x+16 | | -14x-2x=6-7x | | 4x+31=14x-91 | | 6k-4k-5=13 | | x+42=26 | | 88-2x=10x+16 | | (2x-9)(2x+7)=(2x-5)(2x+3) | | M-2=8 | | 6x(-9)= | | 8=x-(-1) |